Methodological Problems of Modern Transportation Logistics - Alexander Kuznetsov (TransNav: International Journal on Marine Navigation and Safety of Sea Transportation, 2018)
The terminology and conceptual apparatus of modern logistics as a scientific discipline is far from being shaped. Researches and developers of legislative and norm-setting documents are obliged to use their own or barrowed terminology, in both case not shared ubiquitously. Consequently, the interpretations even of basic concepts differ significantly. In particular, there exists an academic and practical point of view that refuse the right for existence of the term “transportation logistics”. This clause is explained by the proclaimed omnipresence and universality of logistics, which has in its operational glossary the term “transportation”, treated as a local, subordinated and thus secondary function. This paper tries to set a decisive rule to distinguish between general logistics and transportation logistics, arguing that these two disciplines are well separated by the objects and methodology, knowledge and activities. In transportation logistics defined this way the authors examine two principal components of the transportation processes, storage (warehousing) and movement (shipping). This consideration lead to conclusions that the classical mathematical toolkit is not fitted for the design and management of modern global supply chains.